Optimising assessment of kidney function when managing localised renal masses. Issue 3 (7th August 2017) - Ellis, Robert J; Joshi, Andre; Ng, Keng L; Francis, Ross S; Gobe, Glenda C; Wood, Simon T
Summary:   Increased early and incidental detection, improved surgical techniques and technological advancement mean that the management of renal mass lesions is constantly evolving. The treatment of choice for renal mass lesions has historically been radical nephrectomy. Partial nephrectomy is now recommended for localised renal masses, owing to favourable renal functional outcomes. Ablative renal surgery confers a significant risk of chronic kidney disease. There are few studies assessing long term outcomes of nephrectomy on renal outcomes, and virtually no studies assessing long term outcomes for less invasive therapies such as ablation. Unless a renal mass is clearly benign on imaging, management decisions will be made with an assumption of malignancy. The content of this review applies to both benign and malignant renal mass lesions. We advocate for improved strategies for kidney function assessment and risk stratification, early targeted referral, and regular screening for chronic kidney disease for all patients after surgery.